Rolul abordărilor economice în conturarea politicilor de mediu: Instrumentele orientate spre piață - Raluca Maria VELIŞCU (Revista Transilvană de Ştiinţe Administrative, 2008)
The main assumption of this paper is that the decisions society assumes as a whole regarding the quality of the environment we live in must be based on a broader approach than the one offered by our environmental law and policy. We assume that when an environmental decision is made, few options are considered and few alternatives judged. Other disciplines such as political science, economics, and philosophy can offer good sources of inspiration for environmental public policy. Thus, we present how one of these possible sources, economics, can provide the framework and the foundation for policy decision-making regarding the environment. The “investigation” reveals that economic tools are underestimated as a source of such decisions, mainly because such instruments are complex and difficult to implement and also socially disputed. Our argument is that, with the proper knowledge and expertise, economic solutions are very effective and yield greener results than most instruments we currently use.